18F-labeled PEGylated exendin-4 imaging noninvasively differentiates insulinoma from an accessory spleen: the first case report of [18F]FB(ePEG12)12-exendin-4 positron emission tomography/computed tomography for insulinoma - Sakaki, Kentaro; Murakami, Takaaki; Fujimoto, Hiroyuki; Shimizu, Yoichi; Miyake, Kanae Kawai; Otani, Daisuke; Kiyobayashi, Sakura; Okada, Takuya; Fujimoto, Masakazu; Hakata, Takuro; Yamauchi, Ichiro; Shimada, Kotaro; et al. (Frontiers in Endocrinology, 2023)
Background: Insulinomas are the most common functioning pancreatic neuroendocrine neoplasms, and these tumors induce hypoglycemia due to hyperinsulinemia. Hypoglycemia caused by insulinomas can cause seizures, coma or death due to the delayed diagnosis. The only curative treatment is surgical resection. To perform curative surgical resection of insulinomas, preoperative localization is crucial. However, localization of insulinomas is often challenging using conventional imaging methods such as computed tomography (CT) and magnetic resonance imaging. Although endoscopic ultrasound (EUS) fine-needle aspiration and selective arterial calcium stimulation test, which can reflect the endocrine character of the tumor, are performed in such cases, these modalities are invasive and require operator-dependent techniques. Additionally, somatostatin receptor (SSTR)-targeted imaging has a relatively low sensitivity for detecting insulinomas due to its low SSTR type 2 expression. Thus, there is an urgent need for developing a noninvasive diagnostic technique which is specific for detecting insulinomas. Consequently, glucagon-like peptide-1 receptor-targeted imaging has recently emerged and gained a wide interest. Recently, we have developed a novel 18F-labeled exendin-4-based probe conjugated with polyethylene glycol, [18F]FB(ePEG12)12-exendin-4 (18F-exendin-4), for positron emission tomography (PET) imaging. Here we report a case of insulinoma in which 18F-exendin-4 PET/CT noninvasively provided critical information for localization. Case Description: This is a case of a 58-year-old male with symptomatic hypoglycemia for 10 years; however, a preoperative diagnosis of insulinoma was not established due to the difficulty in differentiating it from an accessory spleen using conventional imaging. Moreover, the patient requested to avoid invasive diagnostic procedures including EUS. 18F-exendin-4 PET/CT revealed significant uptakes in the pancreatic tail whereas no apparent uptakes were observed in the spleen; thus, curative laparoscopic enucleation of the pancreatic tail was performed. The diagnosis of insulinoma was confirmed via histopathological examination. This is the first case report of insulinoma diagnosed using 18F-exendin-4 PET/CT. Conclusion: In this case, PET information led to curative resection through enucleation of the pancreas. 18F-exendin-4 PET/CT may serve as a useful noninvasive clinical tool for insulinoma localization.